(untitled) (Ozone Therapy Global Journal, 2024)
Investigation of a clinical case of a 27-year-old male athlete patient with rupture of the left Achilles tendon, with surgical intervention, with 5 months of evolution, he presented with post-surgical infection and difficulty in healing. Treatment was applied with intravenous ozonated saline solution, antibiogram and subsequently intravenous mesenchymal stem cells, resulting in reduction of inflammation and total closure of the affected area, with complete mobility and functionality of the left foot.